BIODIGESTER IN BEEF CATTLE FEEDLOT - Silva, Leandro de Oliveira; Porto, Petrônio Pinheiro; Porto, Emília de Paiva; da Silva, Marcos Augusto Alves; Mantovani, Tiago Marques; da Silva, Pedro Henrique; Sato, Denis; Coneglian, Amanda Ipólito (Seven Editora, 2025)
This study addresses the implementation of biodigesters in beef cattle confinement systems, an economic activity of great relevance, however, which faces significant challenges in waste management. The research highlights the transformation of waste into valuable resources, such as biogas and biofertilizers, and the promotion of sustainable agricultural practices. Through a systematic literature review and documentary analysis, a theoretical research was carried out, which covered academic literature from several decades. The results indicate that biodigesters offer an effective solution for waste management in beef cattle, contributing to the reduction of waste and harmful emissions and promoting the circularity of resources on the farm. However, the implementation of these systems is not without challenges, including the need for qualified personnel for operation and maintenance, corrosion of equipment by hydrogen sulfide gas, and the complex logistics of livestock management and leachate treatment. Despite these challenges, the integration of biodigesters into beef cattle is a promising approach that offers substantial benefits for crop production and environmental preservation. The adoption of this technology can contribute significantly to the sustainability of beef cattle, turning challenges into opportunities and promoting a more balanced and efficient production model. Continuing these efforts can pave the way for more sustainable farming practices in the future. DOI: https://doi.org/10.56238/sevened2024.037-124